The influence of giving people businesscredit (KUR) on increasing UMKM profit - Atipah, Femi Nurul; Kholiq, Azizah; Halilintar, Halilintar; Haryadi, Haryadi; Rahayu, Sri (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The purpose of this study was to analyze the effect of KUR on increasing micro business profits on KUR customers at Bank BRI Sangeti Unit and to analyze how much influence KUR provides on increasing micro business profits on KUR customers at Bank BRI Sangeti Unit. The method used in this study is quantitative with the research object KUR Bank BRI customers, Sangeti Unit, Muara Jambi Regency, 2022 research year. The popuation in this study were 644 customers and the sample used in this study was 10% of the population, namely 64 customers. the results of the study that there is an influence between the provision of people's business loans on increasing profits of UMKM customers of Sengeti bank units, this is proven by a significance value of 0.000 <0.05 and a large effect of 18.5%. The People's Business Credit Program (KUR) as a whole has been well implemented, therefore it should be maintained so that this program can continue to benefit micro and small businesses in meeting their capital needs and business development, and being able to increase the profits or profits they get from business results. which is executed.